The Effect of Culture on Girl Students Academic Performance in Secondary School of Kabale Municipality Kabale District. - Akasansibwa, Linit C. (Kabale University, 2023)
The major purpose of the study was to investigate the effect of culture on girl student's academic performance in secondary school of Kabale Municipality Ka bale district. This study had the following specific objectives: to investigate the perception of teachers, students, parents and religious leaders on the issues of early marriage to girls, to assess the perceptions of the teachers, students, parents and religious leaders on cultural values of smart girls, to find the general perception of community s expectations of girls.A case study design was adopted. A sum of 80 individuals was used in this study from which 16 were individual teachers, 40 individual students, I6 individual parents, 4 religious leaders, and 4 elders were taken as sample size. The study also found negative effects of the names for smart girls where they even tried to hide their talents so that they may be seen as normal. Names are like Kihember,Batare were demeaning and discouraged girls from trying as hard as boys in their academics. The researcher recommended the strategies which should be put into considerations so as to end up the patriarchy system and other bad cultural norms and values about girls and women, which not only demean them but impede them from struggling to be on equal foot with men.